Treatment of oromaxillofacial fracture in elderly: A literature review: Perawatan fraktur oromaksilofasial pada manula: Tinjauan Literatur - Kasma AS; Andi Tajrin; Hadira (Makassar Dental Journal PDGI Makassar, 2022)
Maxillofacial fracture in elderly patients mostly related to age-related changes and systemic pathologic conditions. However, traumatic injuries in the elderlyhave been increasing in recent years; this is due to increased active life span with advances in medicine that result in a higher percentage of older people in the population. This article ia a review of oromaxillofacial frac-ture in elderly that published since the last 10 years obtained through the search of the electronic database PubMed and Google Scholar, then selected as many as six studies based on the treatment of oromaxillofacial fracture in elderly. Based on the selec-ted literature that has been reviewed, falls were responsible for the majority of fractures in the elderly group. The fracture loca-tions are varied but mostcommon site is zygomatic complex, nasal bone, and condylar. The results of this literature review high-light that majority of elderly patients are treated without surgical procedures.It is concluded that the treatment of maxillofacial trauma in elderly patients is often challenging, as elderly patients require specific attention and multidisciplinary collaboration in the diagnosis and sequencing of trauma treatment.